Glutamate reduces experimental intestinal hyperpermeability and facilitates glutamine support of gut integrity - Vermeulen, Mechteld AR (Baishideng Publishing Group Co., Limited, 2011)
AIM: To assess whether glutamate plays a similar role to glutamine in preserving gut wall integrity. METHODS: The effects of glutamine and glutamate on induced hyperpermeability in intestinal cell lines were studied. Paracellular hyperpermeability was induced in Caco2.BBE and HT-29CL.19A cell lines by adding phorbol-12,13-dibutyrate (PDB) apically, after which the effects of glutamine and glutamate on horseradish peroxidase (HRP) diffusion were studied. An inhibitor of glutamate transport (L-trans-pyrrolidine-2,4-dicarboxylic acid: trans-PDC) and an irreversible blocker (acivicin) of the extracellular glutamine to glutamate converting enzyme, γ-glutamyltransferase, were used. RESULTS: Apical to basolateral HRP flux increased significantly compared to controls not exposed to PDB (n = 30, P < 0.001). Glutamine application reduced hyperpermeability by 19% and 39% in the respective cell lines. Glutamate application reduced hyperpermeability by 30% and 20%, respectively. Incubation of HT29CL.19A cells with acivicin and subsequent PDB and glutamine addition increased permeability levels. Incubation of Caco2.BBE cells with trans-PDC followed by PDB and glutamate addition also resulted in high permeability levels. CONCLUSION: Apical glutamate -similar to glutamine- can decrease induced paracellular hyperpermeability. Extracellular conversion of glutamine to glutamate and subsequent uptake of glutamate could be a pivotal step in the mechanism underlying the protective effect of glutamine.